Modulatory Impact of Lamiaceae Metabolites on Apoptosis of Human Leukemia Cells - Berdowska, Izabela; Zieliński, Bogdan; Matusiewicz, Małgorzata; Fecka, Izabela (Frontiers in Pharmacology, 2022)
Lamiaceae species are rich sources of biologically active compounds which have been applied in medicine since the ancient times. Especially their antineoplastic properties have been thoroughly studied with respect to their putative application in chemoprevention and adjuvant therapy of cancer. However, the most known biological effects of Lamiaceae have been ascribed to their essential oil fractions, whereas their (poly)phenolic constituents being also abundant in these plants, are much less recognized, nevertheless contributing to their beneficial properties, such as anti-cancer actions. The aim of this study was to evaluate the impact of dried aqueous extracts from common thyme (Thymus vulgaris) (ExTv), wild thyme (Thymus serpyllum) (ExTs), sweet marjoram (Majorana hortensis) (ExMh), and peppermint (Mentha × piperita) (ExMp), as well as (poly)phenolic compounds: caffeic acid (CA), rosmarinic acid (RA), lithospermic acid (LA), luteolin-7-O-β-glucuronide (Lgr), luteolin-7-O-rutinoside (Lr), eriodictyol-7-O-rutinoside ( Er), and arbutin (Ab), on unstimulated Jurkat cells, in comparison with their effect on staurosporine-stimulated Jurkat cells. Jurkat T cells were incubated with different concentrations of ExTv, ExTs, ExMh, ExMp, Lgr, LA, Er, Lr, RA, CA, or Ab. Subsequently, staurosporine was added to half of the samples and flow cytometry combined with fluorescence-activated cell sorting analysis was conducted, which allowed for the selection of early and late apoptotic cells. Both ExTs and ExMh stimulated apoptosis of Jurkat cells and enhanced the proapoptotic effect of staurosporine. Conversely, ExTv and ExMp demonstrated no clear effect on apoptosis, regardless of the cells’ death induction or not by staurosporine. Lr, RA, and especially CA raised the staurosporine-induced apoptotic effect. The impact of Er, Lgr and Ab on Jurkat cells showed fluctuations depending on the compound concentration. Neither Er nor Ab altered staurosporine-induced apoptosis in Jurkat cells, whereas Lgr seemed to weaken proapoptotic action of staurosporine. The most evident observation in this study was pro-apoptotic action of polyphenolic mixtures derived from Thymus serpyllum and Majorana hortensis, and enhancement of staurosporine-induced apoptosis by caffeic and rosmarinic acids. Therefore, it might be concluded that these are the mixtures of biologically active polyphenols which often exert more pronounced beneficial effects than purified molecules.